Animal Health and Disease Investigation for Stock Inspectors and Animal Managers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
B Cottam and J Berry 1998. 276 pp.ISBN 0 7345 0013 0 Australian$30 (Euro 17.60)Department of Primary Industries publications,GPO Box 46, Brisbane Q 4001, Australia.Fax: +61 7 32 39 65 09Email: books@dpi.qld.gov.au